Formarsi nel calcio, tra ieri e oggi - Mariani, Alessandro (Studi sulla Formazione/Open Journal of Education, 2023)
After a concise reconstruction of the main key moments that have characterized the history of football, this contribution analyzes the multiple articulations of contemporary football, highlights its polymorphism, its complexity and its contradictions. From this route, which ends with the analysis of a “case study”, the remarkable cultural richness and the extraordinary educational scope of the most popular sport in the world clearly emerge.